(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
Many researchers adopted the quasi static roll over testing in the calculation of a prototype prosthetic feet roll over shape. In this work, the prototype of a new carbon fiber prosthetic foot was tested for roll over characteristic. An inverted pendulum like apparatus has been built to achieve the required test, and the prosthesis roll over shape calculated. Roll over characteristics were estimated as: effective radius of curvature about 202mm, center of curvature of 26.55mm, and the forward travel against shank angle was plotted.